Algirdas Mošinskis and Jurgis Getneris in the Context of Heritage Protection in Interwar Lithuania - Motuzas, Robertas (Lietuvos istorijos studijos, 2018)
In interwar Lithuania, issues of heritage protection were analyzed from the perspective of the official institutions of heritage protection; so, in many cases, the contribution of intellectuals engaged in highlighting the issues of heritage protection was not disclosed. Artist Mstislavas Dobuzinskis, general Vladas Nagevicius, bibliographer and archeologist Eduardas Volteris, art critic Paulius Galaune, historian Zenonas Ivinskis etc. had discussed, promoted and expressed concerns about heritage protection. However, approaches to heritage protection, peculiar for their modern and innovative insights by A. Mosinskis and J. Getneris, can be distinguished out of the numerous opinions expressed by the intellectuals. Despite a unique contribution of the architects to interwar heritage protection, their heritage protection activities have not been broadly researched and evaluated.The aim of this article is to analyze the approaches of A. Mosinskis and J. Getneris to heritage protection and their influence on the heritage protection discourse in interwar Lithuania.An analysis and evaluation of the contribution of A. Mosinskis and J. Getneris to heritage protection in interwar Lithuania have shown that papers by the architects, dedicated to heritage protection topics, changed the heritage protection discourse in interwar Lithuania by initiating a shift from elementary heritage protection principles toward heritage protection approaches common to a complex structural heritage protection concept. The architects cultivated the principles of sustainable urban development and integrity, suggested complex ideas of cultural heritage protection and refused to protect only unique single objects.
Keywords: protection of cultural heritage; architectural heritage; townscape; landscape; A. Mosinkis; J. Getneris